Korean Students in the United States - Kim, Hanna (International Higher Education, 2011)
Ongoing globalization efforts in Korean society have increased the value of a U.S. college education, giving applicants the greatest competitive edge in the job-searching process. Diverse cultural experience and a sound understanding of the English language are a few of many benefits of studying in the U.S.–qualities Korean corporations are looking for in prospective employees. As the number of Korean students seeking U.S. college degrees continues to escalate, it is imperative that they become able to utilize the opportunities granted by such an experience.